Pengaruh Motivasi dan Disiplin Kerja terhadap Prestasi Kerja Aparatur Sipil Negara pada Kantor Kecamatan Cipari Kabupaten Cilacap - Heru Dwi Fitrianto; Nana Darna; Ading Rahman Sukmara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The problems faced in this study include (1) How is motivation related to the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency? (2) How is work discipline related to the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency? (3) How is the influence of motivation and work discipline on the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency? This study aims to study, find out, and analyze (1) The influence of motivation on the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency. (2) The influence of work discipline on the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency. (3) The influence of motivation and work discipline on the work performance of State Civil Apparatus at the Cipari District Office, Cilacap Regency. The method used in this study is an explanatory survey, while the technical data analysis is validity testing, reliability testing, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression (Multiple Regression). The results of the study inform that (1) Motivation has a positive effect on the work performance of state civil servants at the Cipari District Office, Cilacap Regency. This means that if motivation is increased, then the work performance of state civil servants at the Cipari District Office, Cilacap Regency will also increase. (2) Work discipline has a positive effect on the work performance of state civil servants at the Cipari District Office, Cilacap Regency. This means that if work discipline is increased, then the work performance of state civil servants at the Cipari District Office, Cilacap Regency will also increase. (3) Motivation and work discipline have a positive effect on the work performance of state civil servants at the Cipari District Office, Cilacap Regency. This means that if motivation and work discipline are increased, then the work performance of state civil servants at the Cipari District Office, Cilacap Regency will also increase.